Preparation of anti‐corrosive high‐conductivity copper–graphene composite film. (1st July 2018) - Liu, Pengzhong; Chen, Xiaohong; Liu, Ping
Abstract : Copper matrix/graphene composite films were prepared using copper foil as a growth matrix and ethylene as a carbon source. Research results showed that when the concentration of carbon decreased, nucleation density was low and the graphene grains were larger with better boundaries to other grains. A moderate amount of hydrogen assisted decomposition of the hydrocarbons, but also etched some nucleation sites, favourable for the growth of high‐quality graphene. The H2, Ar and carbon source gas (0.931 vol% C2 H4 –Ar mixture) with the flow rates of 70, 4000 and 5 sccm and the growth time of 10 s were the parameters chosen to obtain the copper matrix bilayer graphene composite films. The resulted composite film demonstrated electrical conductivity better than copper. Addition of graphene can greatly improve the corrosion resistance of matrix material. This is true whether in the electrochemical corrosion or immersion corrosion in the oxidation and alkaline environments.